Kyai's Leadership Strategy and Its Implications For Improving The Quality of Education - Muhammad Ghafar (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article results from field research that reveals the kyai's leadership strategy and its implications for improving the quality of education at the Amanatulloh Islamic Boarding School in Banyuwangi. In this study, data analysis was carried out since the data collection was rechecked. The study results concluded that the leadership strategy of K.H. Rouhin Huda in improving the quality of education of the Amanatullah Islamic Boarding School in Banyuwangi is carried out by changing the mindset of human resources. It is improving the quality of teachers and collaborating with businesses, and improving the quality of students/students. Curriculum development. Leadership Implications, K.H. Rouhin Huda in improving the quality of pesantren education, among others, in the dimensions of open communication between members of the organization. Improving innovation and creation in work or pursuing higher education as well as strengthening cohesion between members of the organization and a comfortable organizational climate.